Maternal Vitamin D Status and Small-for-Gestational-Age Offspring in Women at High Risk for Preeclampsia - Gernand, Alison D. (2014)
OBJECTIVE: To examine the association between second-trimester maternal serum 25-hydroxyvitamin D (25[OH]D) concentrations and risk of small for gestational age (SGA) in singleton, live births. METHODS: We assayed serum samples at 12 to 26 weeks of gestation for 25(OH)D in a sample of participants in a multicenter clinical trial of low-dose aspirin for the prevention of preeclampsia in high-risk women (n=792). Multivariable log-binomial regression models were used to assess the association between 25(OH)D and risk of SGA (birth weight less than the 10(th) percentile of gestational age) after adjustment for confounders including maternal prepregnancy obesity, race, treatment allocation, and risk group. RESULTS: Thirteen percent of infants were SGA at birth. Mean (SD) 25(OH)D concentrations were lower in women who delivered SGA (57.9 [29.9] nmol/L0 vs. non-SGA infants (64.8 [29.3] nmol/L, P=0.028). In adjusted models, 25(OH)D concentrations of 50-74 nmol/L and ≥75 nmol/L compared with <30 nmol/L were associated with 43% (95% confidence interval [CI] 0.33-0.99) and 54% (95% CI 0.24-0.87) reductions in risk of SGA, respectively. Race and maternal obesity each modified this association. White women with 25(OH)D ≥50 vs. <50 nmol/L had a 68% reduction in SGA risk (adjusted risk ratio [RR] 0.32, 95% CI 0.17-0.63) and nonobese women 25(OH)D ≥50 vs. <50 nmol/L had a 50% reduction in SGA risk (adjusted RR 0.50, 95% CI 0.31-0.82). There was no association between 25(OH)D and risk of SGA in black or obese mothers. CONCLUSION: Maternal vitamin D status in the second trimester is associated with risk of SGA among all women, and in the subgroups of white and nonobese women.